PEMANFAATAN BERITA VIRAL MEDIA SOSIAL SEBAGAI BAHAN PEMBERITAAN DI POPMAMA.COM - Syabita Salma Nugrani; Amiruddin Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of social media has transformed digital journalism practices, especially regarding the use of viral content as an initial source of information. Popmama.com as a parenting media platform requires a selective editorial strategy to ensure viral issues remain relevant to the needs of Millennial and Gen Z mothers. This study aims to analyze the use of viral social media news as news material at Popmama.com. A descriptive qualitative approach with a case study method was employed to understand the editorial process carried out by the newsroom. Data collection used in-depth interviews, article observation, documentation, and literature study. Research informants consisted of Senior Editors, Editors, Senior Creative Writers, and Creative Writers at Popmama.com. Findings show that the newsroom utilizes TikTok, Instagram, Google Trends, and other analytical tools to monitor viral issues. News processing includes issue selection, fact verification, contextual information enrichment, educational article writing, and editing based on journalistic principles to maintain information quality and the characteristics of digital parenting media.